Long-term endocrine outcomes and quality of life in paediatric and young chronic myeloid leukaemia patients on tyrosine kinase inhibitor therapy: a prospective study from India - Mohan, Rajiv; Nagpal, Chitrakshi; Upadhya, Swasthik; Kumar, Akash; Khadgawat, Rajesh; Bakhshi, Sameer; Pushpam, Deepam (Frontiers in Oncology, 2025)
BackgroundChronic myeloid leukaemia (CML) is rare in paediatric population, approximately 2–3% of leukaemia cases in children and 9% in adolescents. The introduction of tyrosine kinase inhibitors (TKIs) has significantly improved outcomes, but long-term use may lead to adverse endocrine effects and impact quality of life (QoL).MethodsThis prospective cross-sectional study evaluated 82 paediatric and young adult CML patients who were started on TKI therapy at <18 years of age. 71 patients were on TKI for >2 years and 11 patients were initiated on TKI during the study. Anthropometric measurements, Tanner staging, and laboratory parameters assessing endocrine function, bone health, glucose and lipid metabolism were evaluated. QoL was assessed with validated instruments.ResultsMedian duration of TKI exposure was 7.5 years. Short stature was observed in 15% (11/71) of patients. Among those who were prepubertal at TKI initiation, 26.5% (9/34) were found to have short stature. Low Bone mineral density was found in 35·2% (24/68). Vitamin D deficiency was found in 84% and subclinical hypothyroidism in 9·8% (7/71). Two patients had poor sperm quality. One male patient had infertility. There was less impact on glucose, lipid profile, and adrenal function. In the QoL analysis, social functioning was affected among the functional scales, while financial difficulties, appetite loss, and fatigue were impacted in the symptom scales. Overall, QoL scores for physical, psychosocial, and school functioning remained well-preserved, but longer TKI treatment duration was associated to lower scores in these domains.DiscussionThis comprehensive evaluation highlights the need for close monitoring of BMD in patients who are on long-term TKI therapy. Evaluation of all other endocrine functions can be done as clinically indicated.